Faktor Risiko Hernia Nukleus Pulposus Pada Pasien Nyeri Punggung Bawah - Iffah Dzakiyyah Ifmi; Roni Eka Sahputra; Yuliarni Syafrita; Hendra Permana; Syandrez Prima Putra (CV. ITTC INDONESIA, 2026)
This study aimed to analyze the association between age, sex, occupation, smoking status, and body mass index (BMI) with the incidence of lumbar disc herniation (LDH) among patients with low back pain. This analytical observational study used a cross-sectional design with medical record data from 69 patients attending the Orthopedic and Traumatology Clinic at Dr. M. Djamil General Hospital, Padang, from 2020 to 2021. The results showed that 63.8% of patients were diagnosed with LDH. Smoking status (p=0.043; OR=3.21) and BMI (p=0.035; OR=3.39) were significantly associated with LDH, while age, sex, and occupation showed no significant relationship. These findings indicate that smoking and elevated BMI are important modifiable risk factors for LDH, highlighting their role in prevention strategies.